Impact of Stem Cells on Reparative Regeneration in Abdominal and Dorsal Skin in the Rat - Evgeniya Kananykhina; Andrey Elchaninov; Galina Bolshakova (Journal of Developmental Biology, 2024)
A characteristic feature of repair processes in mammals is the formation of scar tissue at the site of injury, which is designed to quickly prevent contact between the internal environment of the organism and the external environment. Despite this general pattern, different organs differ in the degree of severity of scar changes in response to injury. One of the areas in which regeneration after wounding leads to the formation of a structure close to the original one is the abdominal skin of laboratory rats. Finding out the reasons for such a phenomenon is essential for the development of ways to stimulate full regeneration. The model of skin wound healing in the abdominal region of laboratory animals was reproduced in this work. It was found that the wound surface is completely epithelialized on the abdomen by 20 days, while on the back—by 30 days. The qPCR method revealed higher expression of marker genes of skin stem cells (Sox9, Lgr6, Gli1, Lrig1) in the intact skin of the abdomen compared to the back, which corresponded to a greater number of hairs with which stem cells are associated on the abdomen compared to the back. Considering that some stem cell populations are associated with hair, it can be suggested that one of the factors in faster regeneration of abdominal skin in the rat is the greater number of stem cells in this area.